2018
DOI: 10.1002/jor.24074
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Pseudomonas aeruginosa and Staphylococcus aureus biofilms from implant materials in a diffusion dominated environment

Abstract: Antibiotic-loaded calcium sulfate beads (CS-B) are used to treat biofilm-related periprosthetic joint infections (PJI). A previous study has shown that such beads are effective in reducing lawns biofilms grown on agar plates; however, the ability of CS-B to eradicate biofilms grown on solid orthopedic material surfaces has not been investigated. We grew biofilms of bioluminescent strains of Pseudomonas aeruginosa Xen41 and a USA300 MRSA Staphylococcus aureus SAP231 on ultra-high molecular weight polyethylene (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…Group B was subdivided into five groups ( n = 5) and all were contaminated with P. aeruginosa . Two reference strains, A. baumannii (ATCC BAA-1710) and P. aeruginosa (ATCC 27853), were grown on Luria–Bertani media (LB) at 37 °C and overnight cultures were used [20,26]. A suspension with 3 × 10 5 CFU/mL concentration was prepared by spectrophotometer.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Group B was subdivided into five groups ( n = 5) and all were contaminated with P. aeruginosa . Two reference strains, A. baumannii (ATCC BAA-1710) and P. aeruginosa (ATCC 27853), were grown on Luria–Bertani media (LB) at 37 °C and overnight cultures were used [20,26]. A suspension with 3 × 10 5 CFU/mL concentration was prepared by spectrophotometer.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…However, to the best of our knowledge, this is the first report that shows the ability of L. monocytogenes to form biofilms on ultra-high molecular weight polyethylene used for prosthetic implants. Polyethylene has been shown to support biofilms of two clinically significant organisms, Pseudomonas aeruginosa and Staphylococcus aureus , and after antibiotic treatment, polyethylene showed no viable cells for these organisms from the material surfaces after a 24-h exposure 68 . However, the same study demonstrated that viable cells could be recovered from the antibiotic-treated biofilms after 72-h of exposure, implying a state of protection or dormancy of biofilm cells.…”
Section: Discussionmentioning
confidence: 99%
“…The development of novel antibiotic or small molecule delivery systems may be a successful strategy to target biofilm formation and improve infection eradication. Both resorbable and nonresorbable antibiotic carriers such as polymethylmethacrylate or calcium sulfate, respectively, have been shown to increase local antibiotic concentrations well above MIC values for many different antibiotic combinations in vitro 115,116 . These local delivery systems are frequently used in the setting of PJI; however, there is no strong evidence to support their ability to improve eradication of clinical infection.…”
Section: New Advancements In the Treatment Of Musculoskeletal Infectionmentioning
confidence: 99%
“…Both resorbable and nonresorbable antibiotic carriers such as polymethylmethacrylate or calcium sulfate, respectively, have been shown to increase local antibiotic concentrations well above MIC values for many different antibiotic combinations in vitro. 115,116 These local delivery systems are frequently used in the setting of PJI; however, there is no strong evidence to support their ability to improve eradication of clinical infection. For example, the use of gentamicin impregnated beads and/or sponges resulted in increased failure after debridement and implant retention for acute…”
Section: Novel Antibiotic Strategiesmentioning
confidence: 99%